Pelatihan dan Pendampingan Penyusunan Rencana Bisnis Model Canvas pada TKML di Kabupaten Mempawah - Singgih Tiwut Atmojo; Irba’ Muhlas Sambodo; Nugra Irianta Denashurya; Gunadi Gunadi; Eko Wahyu Junaidi (Lembaga Pengembangan Kinerja Dosen, 2025)
This PKM is carried out to provide assistance for TKML programs from KEMENAKER RI in Mempawah Regency to develop business using the Business Model Canvas (BMC) method approach. Business mapping is carried out by implementing nine BMC steps. The training process is carried out online and offline as well as direct visits to each TKM. Activities are carried out by discussing BMC by academics who are carrying out PKM, and then presenting the results of the discussion in the forum. The results of this training process are that participants understand their business processes, can map the businesses they run using the BMC method and can gradually increase sales and profits from the businesses they run. In the long term, it is hoped that TKM can be implemented sustainably in order to develop their businesses and also create new SMEs/Businesses that are able to compete in the business world in the future.